Acceptance of ambivalent sexism in trainee teachers in Spain and Latin America countries - Bonilla-Algovia, Enrique (Anales de Psicología / Annals of Psychology, 2021)
Ambivalent sexism is a multidimensional construct composed of two elements: hostile sexism and benevolent sexism. The main aim of this study is to analyse the acceptance of ambivalent sexist attitudes in a sample of future teachers from Spain and Latin America. The sample is composed of 2798 trainee teachers, and their mean age is 22.62 years (SD = 6.23), they were residing in seven countries: Spain, El Salvador, Nicaragua, Colombia, Chile, Argentina and Mexico. The results show that ambivalent sexist attitudes existed ‒to a varying degree‒ in future teachers of every country. The assumption of sexism varies significantly between men and women and among countries. There seems to be a relationship between levels of sexism with indices of gender inequality and human development. Sexist attitudes of teachers can be transmitted through the education system and the socialization process, so including gender issues in initial and in-service teacher training plans is essential.